The Effect of Using Physical Exercises Using Different Speed Resistance, Explosive and Speed – Strengths In Soccer Players Under 19 Years Old - Selim, Mohammed; Khadem, Mohammed (Journal of Physical Education, 2020)
The research aimed at designing exercises using different resistance in soccer players under 19 years old as well as identifying the effect of these resistances on some physical abilities development in soccer players under 19 years old. The researchers used the experimental method on (24) players. Field procedures included physical abilities tests followed by the main experiment (varied resistance style) including plyometrics, rubber ropes, and sand floor exercises then ended with posttests. The researchers collected the data and treated it using SPSS to conclude significant differences between pre and posttests in explosive speed and strength while there are no differences in strength – speed. The researchers concluded that these exercises have positive effects on the subjects under study. Finally, they recommended using these exercises on soccer players of all age groups as well as making similar studies on other physical abilities, basic skills, physiological variables, and other sports.